Kalurahan Incentive Fund in Bantul Regency: A Governmentality Perspective - Condrodewi Puspitasari; Hari Saptaning Tyas; Analius Giawa (Jurnal Ragam Pengabdian, 2026)
Bantul Regency, Yogyakarta implemented the Dana Insentif Kalurahan (DIKal) policy inspired by the Dana Insentif Daerah (DID) policy, which is given by the central government to districts/cities with the best performance assessment. Each villages must get the required performance criteria, and the village with the best performance will received DIKal as a reward. In 2022, from 75 villages in Bantul, only 7 villages received DIKal and in 2023, this increased to 31 villages that received it, with tiered incentive amounts. Even though village received DIKal in a very competitive ways, village cannot freely used these incentives because they must still refer to the district regulations. The aim of this research is to find out how DIKal policies implemented and seen from a governmentality perspective. This research used a qualitative method with an interpretative approached. The results of this research that the DIKal policies implemented in a technocratic way even though the assessment stage is packaged with a democratic model because an independent assessment stage by villages with a score weighting up to 80%. The enthusiasm of villages government in implemented DIKal policies varies greatly. For village that have orderly administration, DIKal policy is joyfull welcomed because it can increased village income. For village that lack order in administration, DIKal is interpreted as a burden because they must completed so many documents. Meanwhile, for village that already have high village income, incentive rewards are no longer an attraction, and DIKal is interpreted only as a mandatory that must be implemented.